Pengaruh Kemudahan Sistem, Keamanan Sistem dan Tampilan Aplikasi Mobile Banking terhadap Kepuasan Nasabah dengan Kualitas Layanan Sebagai Variabel Intervening - Mustika Raudhatul Jannah; Siregar, Suzanna Lamria (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This study aims to analyze the influences of System Easiness, System Security and Application Display of Mobile Baking on Customer Satisfaction with Service Quality as intervening variable. this study uses kuantitative method . Respondents are obtained through the distribution of questionnaires in the form of google forms via Whatsapp and Instagram direct message. The number of respondents satisfies the criteria for mobile banking users is 106 people, consisting of 70 men and 36 women. Hypothesis testing was carried out using Inner Model and Outer Model approach based on Partial Least Square (PLS). The results of study indicate that the system security and application display through service quality have a positive effect on customer satisfaction of mobile banking. On the other hand, the ease of system does not affect the customer satisfaction of mobile banking